This answer is restricted. Please login to view the answer of this question.

Login NowLet us explain, without using a truth table, why (p ∨ q ∨ r) ∧ (¬p ∨ ¬q ∨ ¬r) is true when at least one of p, q, and r is true and at least one is false, but is false when all three variables have the same truth value.

If at least one of p, q and r is true then the disjunction (p ∨ q ∨ r) is true. If at least one of p, q and r is false, then the disjunction (¬p ∨ ¬q ∨ ¬r) is true. Therefore, in this case the conjunction (p ∨ q ∨ r) ∧ (¬p ∨ ¬q ∨ ¬r) is true.

If all three variables have the same truth value equal to true then the value of disjunction (¬p ∨ ¬q ∨ ¬r) is false, and hence the conjunction (p ∨ q ∨ r) ∧ (¬p ∨ ¬q ∨ ¬r) is false.

In the case when all three variables have the same truth value equal to false then the value of disjunction (p ∨ q ∨ r) is false, and hence the conjunction (p ∨ q ∨ r) ∧ (¬p ∨ ¬q ∨ ¬r) is false.

If you found any type of error on the answer then please mention on the comment or report an answer or submit your new answer.

Click here to submit your answer.

HAMROCSIT.COM

## Discussion